Ambulante Hilfe zur Erziehung und Sozialraumorientierung : Plädoyer für ein umstrittenes Konzept der Kinder- und Jugendhilfe in Zeiten der Nützlichkeitsideologie - Seithe, Mechthild; Heintz, Matthias (Verlag Barbara Budrich, 2014)
The current political discourse on the "further development and control of child and youth welfare" attempts to discredit and repress outpatient help for upbringing. The present "plea" interferes professionally and politically in this debate. The authors provide a critical assessment of the current situation of child and youth welfare and in particular of educational assistance and trace the process of the debate on the "further development and control of educational assistance". On the basis of detailed description and analysis of the two basic approaches to action in social work (social work in and with the social space on the one hand and individual casework, e.g. educational assistance, on the other), it deals with the question of whether the controversy alleged by politicians between the two approaches to action is technically justified. In this context, the two approaches to action are presented in their history and development and in their different conceptions. In addition to a clear plea for the preservation and consistently professional design of educational assistance in the context of life-world orientation, this also leads to the realisation that social work in general - and especially in times of neo-liberalisation of the social - is subject to the risk of individualisation. On the other hand, within both approaches it is also possible today to fend off this tendency and to act as a critical force in this society. In addition to the technical, ideological and political examination of the new control intentions of politics vis-à-vis aid for education, this book contains detailed descriptions and discussions on various individual topics, among others: - Technical characteristics, action orientations and process design of the action approaches "Outpatient individual case assistance" and "Work in and with the social space" (8.4 and 9.3, 9.4) - What shares does social work itself have in its partly unprofessional state? (Section 4.4) - Presentation and discussion of the concept of "social space orientation" (8.5) - Individualisation: What is this? How can it be avoided? (Chapter 8).